Efesiensi Dan Kapasitas Biosorpsi Logam Cu (II) Menggunakan Sisa Media Jamur Coprinus Comatus Teraktivasi HCl - Chrysty Elesa Hutauruk; Elvi Yenie; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The development of industries that produce volumes of waste produced, which one is copper, Cu (II). Cu (II) can be dangerous and toxic to human and the environment. This study aims to utilize spent mushrooms subsrate (SMS) Coprinus comatus removing Cu (II) metal in electroplating wastewater. Biosorbent spent mushrooms subsrate (SMS) was activated using HCl. Variation concentrations of HCl (0.1; 0.5; and 1 N) in contact activation time 15 minutes. The results show that biosorbent was activated using HCl at concentration 0.1 N in contact activation time 15 minutes has high efficiency is 13.90%. Keywords: Biosorption, spent mushrooms subsrate, concentrations of HCl, contact activation time , Cu (II), electroplating wastewater.